The Effect of Flashcard Media on English Vocabulary Acquisition in Elementary School - Yusuf, Ilham; Akhmad, Enni; Kaaba, Titin Suhartin; Habibie, Alvons; Ayuba, Hasan (English Education Department, 2025)
This study aims to determine the effect of flashcard media on the English vocabulary mastery of fourth-grade students at SDN Matayangan. The research employs a quantitative method with a One Group Pretest-Posttest design. A total of 24 students from class IV were selected as the research sample using total sampling technique. The research instrument consisted of 20 multiple-choice questions, which were administered both before and after the treatment to measure students’ vocabulary mastery. The treatment involved the use of flashcard media as a learning tool during English vocabulary lessons over a period of several sessions. The research findings show an improvement in the students’ vocabulary scores, with an average pretest score of 63.96 increasing to an average posttest score of 78.33. This indicates that students demonstrated better vocabulary understanding after being exposed to flashcard media. The data were analyzed using paired sample t-test through SPSS, which revealed a significance value of 0.000 (< 0.05). This result confirms that there is a statistically significant difference between the pretest and posttest scores. Therefore, it can be concluded that the use of flashcard media had a significant effect on students’ vocabulary mastery. The findings support previous research which suggests that visual media such as flashcards can enhance memory and retention, especially among young learners. The use of colorful and engaging flashcards helped students to associate words with images, making the learning process more effective and enjoyable. This study recommends that teachers incorporate flashcards into classroom instruction as an alternative strategy to improve students’ English vocabulary acquisition. Keywords: flashcards, vocabulary, English, learning outcomes, elementary students